Framing and loss aversion in tax reporting behavior: Evidence from German income tax return data - Markus Diller; Daniela Kühne (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2020)
This paper investigates the presence of framing effects and loss aversion in tax reporting behavior of wage earners using a balanced panel of German income tax return data. Reference dependence and loss aversion suggest that individuals in a perceived loss situation attribute higher value to a given amount of positive change in outcome than individuals in a perceived gain situation do. Applied to tax reporting behavior, taxpayers who perceive their tax situation as unfavorable compared to a given reference point are expected to make greater effort or accept higher costs to prevent or reduce that perceived loss than taxpayers perceiving themselves to be in a favorable situation. Greater effort can in turn be associated with higher reporting aggressiveness. We identify a potential reference point in taxpayers' previous year's outcome and examine whether taxpayers claim higher additional tax deductions in a loss situation than in a gain situation. We use a difference-in-difference approach with a one-on-one matching strategy to analyze reporting behavior. We find that taxpayers in a loss situation claim higher income-related deductions than taxpayers in a gain situation.
Keywords: D91; H24; H26; 650; loss aversion; framing; tax avoidance; nonbusiness tax